HARNESSING CABLE ACCESS TELEVISION AS a TECHNOLOGY OF CARE AND COMMUNITY EDUCATION: THUNDER GAY MAGAZINE'S HIV/AIDS PROGRAMMING (1987–1991). - Demus, Axelle (Historical Journal of Film, Radio & Television, 2025)
This article explores the HIV/AIDS crisis of the 1980s and 1990s through the lens of an LGBTQ2+ community television program aired in Northwestern Ontario, Canada: Thunder Gay Magazine (1987–1991). This article, in particular, argues that cable access television played a pivotal role in disseminating vital information about the developing HIV/AIDS epidemic in Thunder Bay. Framing community television as a technology of care and education, this article investigates the program's HIV/AIDS pedagogies and further analyzes how Thunder Bay's location, as a smaller, peripheral Canadian city impacted Thunder Gay Magazine's HIV/AIDS programming. As a result, this article seeks to reinscribe Thunder Gay Magazine within the historical record, as peripheral cities like Thunder Bay have traditionally been neglected from both cable access histories and popular accounts of the epidemic in Canada, despite the courageous efforts of individuals who harnessed media technologies to fight HIV/AIDS within their local communities.